TACROLIMUS VARIABILITY FACTORS AND INTERPLAY WITH KIDNEY GRAFT FUNCTION - Taneska, Aleksandra Canevska; Trajceska, Lada; Severova, Galina; Rambabova-Bushljetik, Irena; Nikolov, Igor; Shterjova Markovska, Zaklina; Gjorgjievski, Nikola; Spasovski, Goce (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Introduction : This study aimed to evaluate the association between tacrolimus pharmacokinetic variability and graft function and survival during a one-year follow-up period.  Materials and Methods : A prospective study was conducted with 32 kidney transplant patients. Intra-individual variability (CV > 30%) was defined as high. Patients were categorized as slow or fast metabolizers based on the concentration-to-dose ratio (Co/D). The clinical outcome, measured by the change in eGFR, was assessed over a one-year follow-up period.  Results : CV > 30% was found in 12.5% of patients, and low Co/D was observed in 15.6%. Both fast metabolizers and patients with high tacrolimus pharmacokinetic variability (IPV) showed higher creatinine levels after 6 and 12 months, along with lower eGFR values. However, these differences did not reach statistical significance (e.g., 135.11 ± 50.89 vs. 158.29 ± 68.33, p = 0.499; 126.36 ± 45.60 vs. 150.80 ± 58.60, p = 0.322). The reduction ratio of eGFR ranged from -64% to +40%, with a mean reduction of -1.26 ± 20.60%. Fast metabolizers did not show a higher frequency of reduction ratios >20% compared to others (3 [15%] vs. 0 [0%], p = 0.585),nor did those with high tacrolimus variability (3 [14.3%] vs. 0 [0%], p = 0.657). In the predictive model, age remained sole significant factor for tacrolimus variability.  Conclusion : Further follow-up is needed to fully understand the impact of tacrolimus pharmacokinetic variability on kidney graft function. Keywords : kidney transplant, tacrolimus, pharmacokinetic variability, graft outcome